2008
DOI: 10.1007/s10549-008-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil targets PTEN to regulate NFκB for downregulation of anti-apoptotic genes in breast tumor growth

Abstract: The molecular mechanism for the beneficial effect of fish oil on breast tumor growth is largely undefined. Using the xenograft model in nude mice, we for the first time report that the fish oil diet significantly increased the level of PTEN protein in the breast tumors. In addition, the fish oil diet attenuated the PI 3 kinase and Akt kinase activity in the tumors leading to significant inhibition of NFκB activation. Fish oil diet also prevented the expression of anti-apoptotic proteins Bcl-2 and Bcl-XL in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 117 publications
2
82
0
1
Order By: Relevance
“…(65) Also, it was documented that dietary fish oil significantly suppressed the phospho-inositol 3 kinase (PI3 kinase) activity in the breast tumor, resulting in reduced Akt kinase and NF-κB p65 subunit phosphorylation and anti-apoptotic protein expression. In addition, Ghosh-Choudhury T et al (66), showed that the active constituents of fish oil, DHA and EPA, inhibit NF-κB transcriptional activation, resulting in attenuation of the antiapoptotic gene transcription which confirms our results of decreased NF-κB by omega-3 adjuvant treatment.…”
Section: Discussionsupporting
confidence: 89%
“…(65) Also, it was documented that dietary fish oil significantly suppressed the phospho-inositol 3 kinase (PI3 kinase) activity in the breast tumor, resulting in reduced Akt kinase and NF-κB p65 subunit phosphorylation and anti-apoptotic protein expression. In addition, Ghosh-Choudhury T et al (66), showed that the active constituents of fish oil, DHA and EPA, inhibit NF-κB transcriptional activation, resulting in attenuation of the antiapoptotic gene transcription which confirms our results of decreased NF-κB by omega-3 adjuvant treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Preparation of Cell and Tumor Lysates-Excised tumors were homogenized as described previously (10,24). Briefly, the tumors were lysed in RIPA buffer (20 mM Tris-HCl, pH 7.5, 150 mM NaCl, 5 mM EDTA, 1 mM phenylmethylsulfonyl fluoride, 0.05% aprotinin, and 1% Nonidet P-40).…”
Section: Methodsmentioning
confidence: 99%
“…Transfection and Luciferase Activity-MDA-MB-231 mammary cancer cells were transfected with the indicated expression vectors and luciferase reporter constructs using FuGENE HD as described previously (24,26,27). Cell lysates were used for immunoblotting or luciferase assay as described previously using the luciferase assay kit (24,26,27).…”
Section: Rna Extraction and Real Time Rt-pcr-totalmentioning
confidence: 99%
“…No presente estudo não foi verificada a translocação dessa proteína após estímulo com DHA por 18 horas. Pesquisas mostram que o DHA e o EPA diminuem significativamente a ligação de NFkB ao DNA em células MDA-MB-231 (45,46), corroborando com os nossos achados. Além disso, Horia e colaboradores (47) mostraram que o DHA é capaz de diminuir a expressão gênica de NFkB em MDA-MB- inicia-se a partir de 6 horas de tratamento e estende-se até 24 horas.…”
Section: Discussionunclassified